Reasons For the Dental Implant Failure and Its Complications – A Literature Review - Shalini S, Priscilla; S, Bhuminathan; Prasanna S, Lakshmi; S, Nithyapriya (Journal of Neonatal Surgery, 2025)
Dentists are increasingly integrating artificial intelligence into their practices as technology advances around the world. Dental implant placement is constantly being refined by dentists. In the past few decades, dental and facial implants have evolved from being a hopeful possibility into one of the most rewarding solutions for patients and healthcare professionals. There is a high success rate for implant-supported restorations over the long term. Many clinicians view complications and implant failures as major obstacles to implant treatment, despite their success. While implant therapy has made some improvements, it still relies on biological healing and integration. Implants and complications can result from these intricate biological processes, which can be affected by local or systemic factors. Effectively managing patients with certain risk factors and being ready to handle any difficulties or failures are critical for dental professionals and implant surgeons. The purpose of this article is to examine typical issues related to implant failure, talk about how to handle them, and offer advice to medical professionals regarding implant placement and repair